Coherent current states in a two-band superconductor - Yerin, Y.S.; Omelyanchouk, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Homogeneous cur rent states in thin films and Josephson current in superconducting microbridges arestudied within the frame of a two-band Ginzburg–Landau theory. By solving the coupled sys tem of equations for two order parameters the depairing current curves and Josephson current-phase relation are calculated for different values of phenomenological parameters g and h. Coefficients g and h de scribe the coupling of order parameters (proximity effect) and their gradients (drag effect), respectively. For definite values of parameters the dependence of cur rent j on superfluid momentum q contains local minimum and corresponding bistable states. It is shown that the Josephson microbridge from two-band superconductor can demonstrate p-junction behavior.